ACCURACY ORDER OF THE ACQUISITION OF THE ENGLISH ARTICLE SYSTEM: EVIDENCE FROM THE WRITTEN AND ORAL PRODUCTION OF UNDERGRADUATE ARAB EFL LEARNERS - Muftah, Muneera (Premise: Journal of English Education and Applied Linguistics, 2023)
The present study investigates the accuracy order and underlying processes of acquiring English articles by 45 undergraduate Arab EFL learners drawn from three proficiency groups. The theoretical approach adopted here is Bickerton's (1981) semantic model that focuses on the features Specific Referent(SR) and Assumed Known to the Hearer (HK). The study aims to identify what the three measures, SOC (Supplied in Obligatory Contexts), TLU (Target-Like Use), and UOC (Used in Obligatory Contexts), reveal about the accuracy order of the acquisition of English articles in the written and oral production tasks. It also seeks to determine the semantic contexts in which the articles are overgeneralized and the most challenging context to acquire. The results show that the SOC measure reveals an accuracy order of a >the > and the >a >, whereas the TLU measure reveals an accuracy order of the>a> across the groups. In addition, the UOC measure reveals that goes through a flooding-then-trickling process, then experiences a U-shaped behavior highlighted by an overgeneralization stage, and follows the by undergoing a U-shaped development. Furthermore, the learners have difficulty distinguishing [HK] and [Countability]. The accuracy comparison in article use showed that [+SR, ?HK] and [?SR, +HK] were the most challenging contexts to acquire.